Effect of standardized cranberry extract on the activity and expression of selected biotransformation enzymes in rat liver and intestine - Bártíková, Hana; Boušová, Iva; Jedličková, Pavla; Lněničková, Kateřina; Skálová, Lenka; Szotáková, Barbora (Molecules (Basel, Switzerland), 2014)
The use of dietary supplements containing cranberry extract is a common way to prevent urinary tract infections. As consumption of these supplements containing a mixture of concentrated anthocyanins and proanthocyanidins has increased, interest in their possible interactions with drug-metabolizing enzymes has grown. In this in vivo study, rats were treated with a standardized cranberry extract (CystiCran®) obtained from Vaccinium macrocarpon in two dosage schemes (14 days, 0.5 mg of proanthocyanidins/kg/day; 1 day, 1.5 mg of proanthocyanidins/kg/day). The aim of this study was to evaluate the effect of anthocyanins and proanthocyanidins contained in this extract on the activity and expression of intestinal and hepatic biotransformation enzymes: cytochrome P450 (CYP1A1, CYP1A2, CYP2B and CYP3A), carbonyl reductase 1 (CBR1), glutathione-S-transferase (GST) and UDP-glucuronosyl transferase (UGT). Administration of cranberry extract led to moderate increases in the activities of hepatic CYP3A (by 34%), CYP1A1 (by 38%), UGT (by 40%), CBR1 (by 17%) and GST (by 13%), while activities of these enzymes in the small intestine were unchanged. No changes in the relative amounts of these proteins were found. Taken together, the interactions of cranberry extract with simultaneously administered drugs seem not to be serious.
Keywords: krysa rodu Rattus; střeva; Vaccinium macrocarpon; Male; Biotransformation; Animals; biotransformace; Intestines; Liver; mužské pohlaví; játra; Plant Extracts; potkani Wistar; Rats, Wistar; rostlinné extrakty; zvířata; Rats